Unmet needs in the management of hereditary angioedema from the perspective of Brazilian patients - Pedro Giavina-Bianchi, MD, PhD; Mara Giavina-Bianchi, MD, PhD; Raquel de Oliveira Martins; Maria Cristina Fortunato, PharmD; Ana Claudia Guersoni, MD, PhD (World Allergy Organization Journal)
Introduction: Hereditary angioedema (HAE) is a rare genetic disease characterized by recurrent, potentially life-threatening angioedema episodes. Despite its severity, including the risk of asphyxiation, HAE often remains underdiagnosed. The disease significantly impacts patient quality of life (QoL), leading to anxiety, depression, and avoidance behaviors due to the unpredictable nature of attacks. Understanding the perspectives of patients is crucial for identifying unmet needs in managing this complex condition. Objective: This study aimed to gather real-world insights from Brazilian patients with C1 inhibitor deficiency HAE to identify their unmet needs and assess their perceptions of the effectiveness of current care in preventing and treating HAE attacks. Methods: A cross-sectional study utilized a SurveyMonkey questionnaire distributed to HAE patients through ABRANGHE via email. Participants provided informed consent, and their responses were anonymous. The questionnaire, developed with input from experts and patients, covered aspects of HAE diagnosis, treatment experiences, and QoL assessments. Results: The survey included 178 HAE patients, predominantly female (81%), aged 30–50 years (58%), and college-educated (62%). The most common HAE defect was C1–INH deficiency (53%), followed by HAE-nC1INH (23%), with nearly a quarter unaware of their specific defect. Diagnosis delays were prevalent, with a significant number reporting 13–50 attacks annually (33%) and 15% experiencing more than 50 attacks per year. Laryngeal involvement was reported by 26% of respondents. Most patients (69%) attended regular follow-ups, with 72% on prophylactic treatment and 67% managing acute attacks. The most used acute treatment was Icatibant (49%), followed by pdC1INH (24%). However, confusion regarding medication use persisted, with 45% incorrectly believing that oral medications could effectively treat attacks. Key unmet needs identified included improved access to emergency rooms during attacks (73%), better availability of prophylactic treatment (69%), and enhanced access to specialized care (63%). Patients also emphasized the need for psychological support, increased awareness of HAE, and educational initiatives for patients and healthcare providers. Discussion: This study highlighted significant challenges in HAE management among Brazilian patients, particularly concerning delayed diagnosis, misconceptions about treatment, and inadequate access to specialized care and prophylactic treatments. The high frequency of emergency room visits underscores the difficulties in managing the disease. The substantial burden of HAE on QoL emphasizes the urgent need for improved physician education, streamlined diagnostic processes, and equitable access to effective medications and specialized care facilities. Addressing these gaps is crucial to better support HAE patients, improve diagnostic timeliness, enhance treatment efficacy, and ultimately enhance the overall quality of life for individuals living with HAE.